The Role of Promotion in Increasing Tourist Visits to Telaga Saat Puncak Destination, Bogor, West Java - Dela Safitri; Rizki Nurul Nugraha; Tevila Akwila; Vanny Chang Nurmanto (West Science Social and Humanities Studies, 2024)
This research aims to analyze the role of Telaga Saat's promotional strategy. Telaga Saat is located in Tugu Utara, Cisarua District, Bogor Regency. This research focuses on the importance of the role of promotion in introducing the Telaga Saat destination to visitors, with an emphasis on the BAS method (Branding, Advertising, and Selling), in increasing the number of tourist visits to the Telaga Saat Puncak destination. The research involved analyzing the effectiveness of various promotional campaigns, including branding approaches to strengthen the destination image, advertising strategies to raise awareness and selling techniques to convert interest into actual visits. The research methods used included direct observation, social media monitoring, interviews with management, and document analysis. A descriptive qualitative approach is used to understand how the role of promotion has an impact as a whole to increase visits to a destination. Branding activities have not been realized because the manager focuses more on selling and advertising. In conducting publications using paid media techniques, owned media, social media, endorse (POSE) and succeeded in increasing the number of tourist visits. The results provide an in-depth insight into the positive impact of the BAS method in increasing tourist visits to Telaga Saat Puncak. The findings in this study can help tourism actors to improve promotional strategies especially in branding, advertising and also selling to increase awareness and encourage visits to this destination.